Voicing The Other : Patrick Sweeting’s Perspective in Jaipong Dancer - Astuti, Epata Puji (Journal of Language and Literature, 2019)
Jaipong Dancer is a novel written by Patrick Sweeting, which raises the subordination issue of women as the other. In this novel, Sweeting represents women as the other in paradox. On the one hand, women are represented as the other who is excluded from the society. On the other hand, women are represented as (the ones who are) strong, exotic and difficult to be overpowered. The problem is how Patrick Sweeting voices women as the other in his novel and the research questions are (1) how women as the other are voiced in this novel, and (2) how the writer’s perspective is related to the problem of women as the other in the novel. To understand the voicing of women as the other by the writer, the researcher uses postcolonial feminism by Gayatri Spivak, especially the concept of white men saving brown women from brown men. Textual analysis method is used to find out the relations and the form of the writer’s voice in the novel. Based on the whole analysis, it can be concluded that women as the other are voiced by the writer as the ones who are strong, exotic and difficult to be overpowered. Through his work, the writer who is assumed doing civilizing mission by voicing the issues related to the subordination of women in the Third World is, in fact, silencing the voice of the Third World women and imprisoned it under the stereotype and prejudice. The perspective which is used by the writer to represent the East is the same as other Orientalists’ perspectives. The voice of women in the Third World as depicted in the novel is created by the Western.Key words: voicing, women, the other